Oxo‐Hydroxoferrate K2−xFe4O7−x(OH)x: Hydroflux Synthesis, Chemical and Thermal Instability, Crystal and Magnetic Structures. Issue 1 (24th January 2019) - Albrecht, Ralf; Hunger, Jens; Block, Theresa; Pöttgen, Rainer; Senyshyn, Anatoliy; Doert, Thomas; Ruck, Michael
Abstract: The reaction of Fe(NO3 )3 ⋅9 H2 O with KOH under hydroflux conditions at about 200 °C produces red crystals of K2− x Fe4 O7− x (OH) x in a quantitative yield. In the crystal structure, edge‐sharing [FeO6 ] octahedra form ∞ 2 [ Fe2 O6 ] honeycomb nets. Pillars consisting of pairs of vertex‐sharing [FeO4 ] tetrahedra link the honeycomb layers and form columnar halls in which the potassium ions are located. The trigonal ( P 3 ‾ 1 m ) and the hexagonal ( P 63 / mcm ) polytypes of K2− x Fe4 O7− x (OH) x show oriented intergrowth. The sub‐stoichiometric potassium content ( x ≈0.3) is compensated by hydroxide ions. K2− x Fe4 O7− x (OH) x is an antiferromagnet above 2 K and its magnetic structure was determined by neutron powder diffraction. Under ambient conditions, K2− x Fe4 O7− x (OH) x hydrolyzes and K2 CO3  ⋅ H2 O forms gradually on the surface of the K2− x Fe4 O7− x (OH) x crystals. Upon annealing at air at about 500 °C, the potassium atoms in the columnar halls start to order into a superstructure. The thermal decomposition of K2− x Fe4 O7− x (OH) x proceeds via a topotactic transformation into K1+ x′ Fe11 O17, adopting the rhombohedral β'' or the hexagonal β‐aluminate‐type structure, before γ‐Fe2 O3 is formed above 950 °C, which then converts into thermodynamically stable α‐Fe2 O3 . Abstract : Call to order : Reaction of Fe(III) nitrate in approximately 40 m potassium hydroxide leads to oxo‐hydroxoferrate(III) K2− x Fe4 O7− x (OH) x . This compound shows an unusual vacancy ordering and decomposes topotactically into β'' or β‐aluminate‐type K1+ x′ Fe11 O17 .